Heart and spiritual well-being - Hossein Jalaei Nobari (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. An important type of well-being, which is more valuable and critical than other ones, is spiritual well-being. Other types of well-being are in fact the prerequisite of achieving spiritual well-being and utilizing spiritual virtues that are accepted by any human being. Indeed, spiritual well-being is directly associated with the bliss in the world and the hereafter. Thus, it is more precious than other types of well-being. In this regard, heart is considered the container of spiritual well-being.For downloading the full-text of this article please click here. Please cite this article as: Jalaei Nobari H. Heart and spiritual well-being. J Res Relig Health. 2019; 4(5):1- 4.